The Effect of Multi-Media Instructional Design based on Sweller's Theory on Reducing Cognitive Load and Developing Scientific Concepts among Deaf Primary Students - Aliah M. Al Atiyat (Sultan Qaboos University, 2018)
This study aimed to investigate the effect of instructional design of multi-media on reducing cognitive load and the development of scientific concepts among primary school deaf students. It combined the descriptive and quasi-experimental design using an extension of pre-test and post-test experimental-control group design with three groups: an experimental group that was taught the "solar system, stars and galaxies" modules using multimedia software based on the principles of cognitive load theory; a second experimental group was taught the same content using multimedia software but was not based on the principles of cognitive load theory; and a control group that was taught via the textbook. The study sample consisting of 48 male and female deaf students was selected from Al-Amal Institutes at Jeddah, Madinah, and Tabuk. The study used two instruments: scientific concepts test and NASA-TLX scale of cognitive load. The results revealed that the first experimental group outperformed the second and control group students on both measures. However, there was no significant difference between the second experimental and control groups. It is recommended that Sweller's theory and multimedia be used to design curriculum of science to deaf students.